A Rapid Assessment of Pronophilina Reuter, 1896 community structure and diversity in the uppermost cloud forests near timberline in Manu National Park, Peru (Lepidoptera: Nymphalidae, Satyrinae) - José Cerdeña; Oscar Mahecha-J.; Rafal Garlacz; José Arivilca-Pari; Jackie Farfán; Marco Delgado-Coila; Klaudia Florczyk; Vanessa Díaz-S.; Tomasz W. Pyrcz (SHILAP, 2024)
The subtribe Pronophilina Reuter, 1896 is a group of Papilionoidea that is particularly useful for assessing biodiversity and human-made disturbance, especially in cloud forests. This is because of their high diversity, abundance, distribution patterns, ecological fidelity, and usefulness in formulating conservation policies. A rapid assessment (RAP) was conducted on the Pronophilina in two locations in the upper montane area of Manu National Park, southeastern Peru. The assessment included an evaluation of species richness, faunal composition, similarity, and community structure of Lepidoptera in the area. The two locations were only 30 km apart but in different elevations, ranging from 2800 to 3200 m above sea level. The study recorded a total of 1941 specimens of 45 species, with 18 species (40%) belonging to the genus Pedaliodes Butler, 1867, and as many as 1356 individuals (70%) were found in this genus. Some local species were found to be restricted to very narrow elevation ranges at the forest-puna grassland ecotone. The community structure showed good adjustment with the RAD log-normal model in Trocha Unión and with the Zipf-Mandelbrot model in Qurqurpampa, indicating that the sample obtained is representative of well-preserved uppermost cloud forests. The Sørensen similarity index was relatively low, despite the short distance between the two sites and no apparent geographic isolation. Sampling by “Van Someren-Rydon” traps was confirmed as a very effective method for studying